(untitled) (Fiep Bulletin - online, 2015)
Some scientific evidences have been revealing that the physical activity is a basic contributor for the health and wellness. However, the physical inactivity represents an important cause of atony, reduced quality of life and premature death in the contemporaries societies. Besides that, a factor that worries even more is that these sedentary behaviors seem to be being adopted early in the adolescence. The purpose of this study was to avalue the levels of physical fitness of students between 7 and 17 years old of the city of Pelotas, RS. A transversal study was carried through, in a representative sample of student of the city of Pelotas. The sample was composed for: 1089 students of both sex, included in the urban education system of the city. The following physical variety fitness related to the health had been collected and analyzed: flexibility, abdominal resistance and aerobic resistance. Classification criteria for each age and sex were proposed by PROESP/BR (2002). The analysis plan statistics respected the following stages: calculation of measures of central trend and dispersion for continuous variables and the proportional for the categorical variables; bi-varied analysis and analysis adjusted through Regression of Poisson. The data had been analyzed in the statistical package Stata 8.0. In relation to the results presented for the tests of aerobic resistance, as much for the boys as for the girls was observed a clear trend of improvement in the results in as decreases the age. The flexibility, on the contrary, had a linear relation between the age and the result of the tests, independent of the sex was not observed. Finally, in the tests of abdominal resistance an increase of the reach of the recommendations was evident in as the age decreases, independent of the sex. In relation to the results, it is evident the concern with the low levels of physical fitness of the students of the city of Pelotas, having in mind the recognition of the diverse benefits of the physical aptitude for the health.